2015
DOI: 10.1177/0001839215585602
|View full text |Cite
|
Sign up to set email alerts
|

(Un)Tangled

Abstract: We explore the relationship between status and reputation, examining how its dynamics change over time as these two intangible assets coevolve and how reputation and status are influenced by participation in highly visible events. Using a sample of more than 400 newly founded venture capital (VC) firms, we find that reputation and status positively influence each other but that reputation has a greater effect on status, particularly when firms are older. We also find that the effect of past status on current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 87 publications
0
51
0
Order By: Relevance
“…It also vanishes when crossing national borders. The negative effect of distance from prospective VC investors on the demand for VC varies with the characteristics of those VC investors in terms of their ownership and governance Dimov and Gedajlovic, 2010) and reputation (Nahata, 2008;Pollock et al, 2015;Sorensen, 2007). Independent (i.e., US-style) VC investors have a strong positive effect on the demand for external equity in a radius of 250 km, while for governmental VC investors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It also vanishes when crossing national borders. The negative effect of distance from prospective VC investors on the demand for VC varies with the characteristics of those VC investors in terms of their ownership and governance Dimov and Gedajlovic, 2010) and reputation (Nahata, 2008;Pollock et al, 2015;Sorensen, 2007). Independent (i.e., US-style) VC investors have a strong positive effect on the demand for external equity in a radius of 250 km, while for governmental VC investors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work reveals two routes to status: prestige and dominance (Cheng et al, 2013; Henrich & Gil-White, 2001). Our work focused on the prestige path, which emphasizes that status accrues for members who increase their value to the group and do not minimize others in the group (Anderson & Kilduff, 2009a, 2009b; Flynn et al, 2006; Pollock et al, 2015; Ridgeway & Diekeman, 1989). For example, prior evidence has found that people who are competent (Anderson & Kilduff, 2009a), possess valuable skills and specialized knowledge (Berger et al, 1972), and exhibit helpful and altruistic behaviors (Flynn et al, 2006; Hardy & Van Vugt, 2006) are likely granted high status.…”
Section: Discussionmentioning
confidence: 99%
“…That is because the value created by platforms is inherently co-created by complementors-independent organizations or individuals that provide complementary goods and services (Eisenmann et al, 2011). Affiliation with high-status complementors-that is, complementors that are members of the high-status group in their organizational field-can provide an important source of legitimacy of platforms because it implies a positive legitimacy judgment (Pollock, Lee, Jin, & Lashley, 2015) and stakeholders generally place a strong weight on positive legitimacy judgments by high-status organizations (Pollock, Chen, Jackson, & Hambrick, 2010). High-status complementors' decision to join a platform ecosystem thus implies a positive evaluation of the platform' legitimacy-thereby increasing the platform's legitimacy in the eyes of other stakeholder groups.…”
Section: The Moderating Role Of High-status Complementorsmentioning
confidence: 99%